Partitioning of Volatile Halocarbons between Surrogates for Atmospheric Solid Aerosols and Gas Phase as Examined by TPD MS and Inverse Gas Chromatography - Bogillo, V.I.; Bazylevska, M.S.; Mischanchuk, B.G.; Pokrovskiy, V.A. (Хімія, фізика та технологія поверхні, 2010)
The desorption non-isothermal kinetics of preliminary adsorbed Cl, Br, and I-containing volatile halocarbons from the surface of surrogates for atmospheric solid aerosols (fumed silica and alumina, silica gel and H-mordenite) was studied by TPD MS. The TPD spectra demonstrate high heterogeneity of the surface studied. The average desorption activation energies and half-widths of the halocarbons desorption energy rectangular distribution were calculated. The relationships between the average desorption activation energies and molecular descriptors for the halocarbons were derived for the solids. The partitioning of the halocarbons and additional volatile organics between surrogates for mineral and carbonaceous atmospheric aerosols (silica gel, Carbopack S, Carbosil) was examined by using the inverse gas chromatography method. These data indicate to the energetic heterogeneity of the solid surfaces. The average adsorption energies and variances of the adsorption energy rectangular distribution were calculated and connected with molecular descriptors of the volatiles. A relationship is observed between average desorption activation energies of halocarbons on the silica gel surface from TPD MS data and average adsorption energies in these systems determined using inverse gas chromatography method at finite concentrations.